Treatment of Helicobacter pylori Infection 2011 - O'Morain, Colm; Mc Namara, Deirdre; O'Connor, Anthony (My University, 2011)
This article reviews the literature published pertaining to Helicobacter pylori eradication over the last year. The general perception among clinicians and academics engaged in research on H. pylori has been that eradication rates for first-line therapies are falling, although some data published this year have cast doubt on this. The studies published this year have therefore focussed on developing alternative strategies for the first-line eradication of H. pylori. In this regard, clear evidence now exists that both levofloxacin and bismuth are viable options for first-line therapy. The sequential and ?concomitant? regimes have also been studied in new settings and may have a role in future algorithms also. In addition, data have emerged that the probiotic Saccharomyces boulardii may be a useful adjunct to antibiotic therapy. Other studies promote individualized therapies based on host polymorphisms, age, and other such demographic factors. Over the last decade, it has been widely reported that the success of Helicobacter pylori eradication treatment is falling. A steady decline was observed in the number of patients achieving eradication with standard first-line triple therapy of two antibiotics and a proton pump inhibitor [1?3]. It now appears that the first-line eradication therapies most commonly used in everyday clinical practice fall considerably short of the 80% intention-to-treat (ITT) eradication rates that are considered the minimal acceptable levels as recommended in the Maastricht guidelines [4]. Interestingly, two studies emerged from Asian centers in the last 12 months, which show that, in this part of the world at least, eradication levels using standard therapies remain close to 80%. A Malaysian study showed a standard 1-week pantoprazole, amoxycillin, and clarithromycin regimen to be well tolerated and highly efficacious with a per-protocol eradication rate of 84% [5]. A Japanese study showed remarkably consistent per-protocol eradication rates from 2001 to 2009 fluctuating between 75 and 78% for standard 7-day triple-therapy regimens [6]. A limit of many studies especially those including clarithromycin or levofloxacin is that H. pylori susceptibility to the drugs, which is the main prediction of failure, was not tested.
PUBLISHED
Keywords: Immunology; Infection; Helicobacter pylori; Immunology, Inflammation & Infection; HELICOBACTER PYLORI INFECTION; Health